Development and characterization of a hidden anode-based plasma contactor - Freestone, Tait H., author; Williams, John D., advisor; Yalin, Azer, committee member; Roberts, Jacob, committee member (Colorado State University. Libraries, 2025)
The use of high-current, high-energy electron beams on spacecraft can result in excessive positive electrostatic charging beyond passive mitigation capabilities, potentially terminating beam emission. To counteract this, active charge mitigation via positive ion emission is necessary. This thesis evaluates the Hidden Anode Plasma Contactor (HAPC), developed for the University of Michigan's Beam-Spacecraft Plasma Interaction and Charging Experiment (BSPICE), designed specifically for rapid start, active charge mitigation of a sounding rocket mission. This study characterizes the plasma plume generated by the HAPC along with its operational characteristics, while also detailing the Krypton gas feed system and associated electronics. Ion current production required for the mission was verified through current density measurements and pulse bias testing. Measurements revealed a near-hemispherical plasma expansion, ion energy distributions resembling those of Hall thrusters, and predominant singly charged ions, though multiply charged ions were present. Langmuir probe analysis of the plasma plume downstream of the HAPC identified two distinct electron populations—thermal electrons and higher-energy primaries emitted directly from the cathode. Anode orifice erosion at high power and expellant utilization above 10% was observed, which would likely limit the lifetime of the HAPC to tens of minutes—times much greater than the 7-minute typical duration of a sounding rocket mission. The findings provide comprehensive insights into HAPC operation for BSPICE and highlight its applicability as an alternative plasma source where Hall thruster-like plume characteristics are desired.
Keywords: spacecraft charging; plasma source